How to measure competition? The role of price dispersion in B2B supply markets. (2016) - Scheffler, Paul; Schiele, Holger; Horn, Philipp
Since the formation of close relationships with suppliers requires a considerable amount of resources, the capacities for such relationships are limited. Thus, recently, research points into the direction that it might not be conducive to unconditionally engage in strategic buyer-supplier alliances. Specifically, in those cases where there is a vivid competition within the supply market, it might not be necessary to cooperate closely. However, a convenient measurement method for competition has been missing in the literature so far. Accordingly, this conceptual paper translates insights from the field of economics for an application in purchasing and supply management. It is recommended to evaluate the product price dispersion of supplier quotations in order to assess the intensity of competition in supply markets. As a consequence, this conceptual paper paves the way for future research on competition between suppliers. For managers, the proposed method could support the development of efficient purchasing strategies.